Distribution Features and Health Risk Assessment of Phthalate Pollutants in Facility Soil and Agricultural Products in Xinjiang, China - Haifeng Li; Hejiang Liu; Zhigang Liu; Hanming Su; Silayiding Simayi; Guohong Liu (Agronomy)
To determine the phthalic acid ester (PAE) contents within the soil and agricultural products of facility agriculture in Xinjiang Province, we detected 16 kinds of PAE compounds within 249 soil samples and 203 agricultural product samples through gas chromatography–mass spectrometry. Five PAEs, namely DMP, DEP, DBP, DEHP, and DIBP, were identified in the soil. Their detection rates were found to range from 84.7% to 100%, with total concentrations spanning from 7.29 to 1064.1 μg kg−1 and a mean concentration of 111.8 μg kg−1. The primary PAE pollutants obtained in the soil included DBP, DEHP, and DMP, which accounted for 49.2%, 27.0%, and 12.4% of the total content, respectively. In the agricultural products, six PAEs were detected: DEHP, DBP, DIBP, BMPP, DPP, and DNOP, with detection rates from 3.0% to 46.8% and total contents varying from ND to 5140 μg kg−1 (mean of 637.60 μg kg−1). Among them, DBP, DNOP, and BMPP were the major PAE contaminants in the agricultural products. As demonstrated by a human health risk evaluation, dietary intake of PAEs constituted the primary route of exposure to both non-carcinogenic and carcinogenic risks. DBP and DNOP posed the greatest non-carcinogenic risks to both adults and children; however, the non-carcinogenic risk values for the five PAE congeners in the study area were all less than 1. The carcinogenic risk associated with DEHP was lower than the USEPA-recommended level of carcinogenic risk. Based on these findings, the PAE contents in soil and agricultural products within our study area are not harmful to human health.